The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1557988318790883
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health in Men With Traumatic Spinal Cord Injuries: A Review and Recommendations for Primary Health-Care Providers

Abstract: Sexual health has been well established as a salient priority for men following traumatic spinal cord injury; yet, it continues to be under-addressed by health-care providers in both inpatient and community settings. Given that most men with traumatic spinal cord injuries will be followed by community-based primary health-care providers, including family physicians and nurse practitioners, for their long-term health-care needs, these clinicians are well positioned to address ongoing sexual health issues with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
2
32
0
3
Order By: Relevance
“…The quality of sexual life with interpersonal relations becomes particularly important, especially in persons with a marked reduction of independence [29,30]. Sexual functions are a very important factor in the QOL; recovery of these activities is the highest priority in patients with paraplegia and is in second place of priority in the tetraplegic patients after recovery of hand function [31,32]. Numerous studies have shown that sexual life is one of lower-graded components of the WHOQOL-BREF scale [33][34][35], with lower scores compared to the general population [36].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of sexual life with interpersonal relations becomes particularly important, especially in persons with a marked reduction of independence [29,30]. Sexual functions are a very important factor in the QOL; recovery of these activities is the highest priority in patients with paraplegia and is in second place of priority in the tetraplegic patients after recovery of hand function [31,32]. Numerous studies have shown that sexual life is one of lower-graded components of the WHOQOL-BREF scale [33][34][35], with lower scores compared to the general population [36].…”
Section: Discussionmentioning
confidence: 99%
“…Sexuality is vital in the process of accepting and coping with SCI and highlighted the importance of reproduction for women in general, before and after SCI, were also prominent [10]. Aikman et al [11] reported that lack of sexual rehabilitation services and consensus around clinician roles, and societal stigmas related to disability and sexuality obstruct treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these concerns can worsen ED significantly. Changes in body image representation, depression, anxiety, and fatigue also contribute to worsen ED [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Whether achieved, reflexogenic, psychogenic, or mixed, erection is often short lasting and non-sufficient to maintain satisfactory sexual relations [5,6]. Frequency and quality of sexual activity inevitably decline after SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation